STRATEGI DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3AP2KB) KABUPATEN JEPARA DALAM MENGURANGI TINGKAT PERNIKAHAN DINI - Himmatul ‘Ulya; Rina Martini (Journal of Politic and Government Studies, 2026)
Early marriage is a marriage conducted by a couple or one of the partners who are still categorized as children under the age of 19. Undang-Undang No. 16 Tahun 2019 regulates the minimum age for marriage as 19 years old. However, the number of early marriages in several regions in Indonesia is still quite high, one of which is in Kabupaten Jepara. The number of early marriages in Kabupaten Jepara has fluctuated, indicating that the Pemerintah Kabupaten Jepara, particularly the Dinas Pemberdayaan Perempuan Perlindungan Anak Pengendalian Penduduk dan Keluarga Berencana (DP3AP2KB), has not been able to optimally address this issue. This study aims to analyze the strategies implemented by DP3AP2KB Kabupaten Jepara in reducing the rate of early marriage and to identify the factors that hinder its implementation. This study uses strategic planning theory as the basis for analysis. The research method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observations, and literature studies, while data analysis was carried out through the stages of data reduction, data presentation, and data verification. The results of the study show that the DP3AP2KB of Kabupaten Jepara has implemented various strategies, such as through village or sub-district initiatives for child-friendly environments, the establishment of rumah perlindungan perempuan dan anak at the sub-district level, the creation of a district action plan for child friendly environments, cooperation with external parties, socialization and education for school children, and assistance through the Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak (PPA). However, these strategies have not been optimally implemented, as evidenced by the high number of marriage dispensation requests. The main obstacles encountered include limited human resources, facilities and infrastructure, and budget, suboptimal cross-sector coordination, and low public awareness. Based on the results of this study, it can be concluded that the strategies implemented by DP3AP2KB to reduce the rate of early marriage have not been successful in achieving the expected goals. Therefore, it is necessary to optimize the use of the budget, analyze labor needs, improve the quality of service facilities and infrastructure, strengthen cross-sector coordination, and strengthen strategies to change community behavior.